Kinerja Pegawai dalam Pelayanan Administrasi di Kantor Kecamatan Boliyohuto Kabupaten Gorontalo - Umar Sako Baderan; Yespin Ingo (Publik : (Jurnal Ilmu Administrasi), 2017)
The purpose of this study is to find out how the performance of employees in performing administrative services in Boliyohuto District Office. The research method used is a quantitative approach with correlation method. The result of the writer's observation on the performance of the employees in the administrative service at Boliyohuto Sub-District Office still needs some improvement. Based on the results of research that influence the performance of employees to administrative services in District Boliyohuto Gorontalo Regency, according to the results of testing the hypothesis that the price t arithmetic> of the price register. The closeness of the influence of the performance of employees to the administrative service is shown through calculation of determination that is approximately 40% variation that occurs in the scores of administrative services explained through the variation of employee performance in the district office Boliyohuto Gorontalo District. Improvement of administrative services has a significant (significant) relationship with employee performance through the relationship pattern shown by regression equation = 15 + 0.95X which is very meaningful. In conclusion that every change of one unit on variable X is the employee performance followed by the average change of 0.81 units on variableYyaitu administrative services in the district office Boliyohuto Gorontalo District. Tujuan dalam penelitian ini ialah untuk mengetahui bagaimana kinerja pegawai dalam melakukan pelayanan administrasi di Kantor Kecamatan Boliyohuto. Metode penelitian yang digunakan ialah dengan pendekatan kuantitatif dengan metode korelasi. Hasil pengamatan penulis pada kinerja pegawai dalam pelayanan administrasi di Kantor Camat Boliyohuto masih memerlukan beberapa pembenahan. Berdasarkan hasil penelitian bahwa pengaruh kinerja pegawai terhadap pelayanan administrasi di Kecamatan Boliyohuto Kabupaten Gorontalo, sesuai hasil pengujian hipotesis yaitu harga t hitung> dari harga tdaftar. Keeratan pengaruh kinerja pegawai terhadap pelayanan administrasi ditunjukkan melalui perhitungan determinasi yaitu kurang lebih 40% variasi yang terjadi pada skor pelayanan administrasi terjelaskan melalui variasi kinerja pegawai di kantor Kecamatan Boliyohuto Kabupaten Gorontalo. Peningkatan pelayanan administrasi memiliki hubungan yang signifikan (berarti) dengan kinerja pegawai dengan melalui pola hubungan yang ditunjukkan oleh persamaan regresi = 15+ 0,95X yang sangat berarti. Kesimpulannya bahwa setiap terjadi perubahan satu unit pada variabel X yaitu kinerja pegawai diikuti oleh perubahan rata – rata sebesar 0,81 unit pada variabelYyaitu pelayanan administrasi di di kantor Kecamatan Boliyohuto Kabupaten Gorontalo.